2017
DOI: 10.1021/acs.molpharmaceut.7b00053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biocompatibility Characterization of Red Blood Cell Membrane Targeted and Cell-Penetrating-Peptide-Modified Polymeric Nanoparticles

Abstract: Red blood cells (RBCs) express a variety of immunomodulatory markers that enable the body to recognize them as self. We have shown that RBC membrane glycophorin A (GPA) receptor can mediate membrane attachment of protein therapeutics. A critical knowledge gap is whether attaching drug-encapsulated nanoparticles (NPs) to GPA and modification with cell-penetrating peptide (CPP) will impact binding, oxygenation, and the induction of cellular stress. The objective of this study was to formulate copolymer-based NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Encapsulation process involves isolation of RBCs, loading of drug and infusion into the body for effective delivery and metabolism at the target site. This process involves different surface chemistries, shapes to the surface of RBC and compositions which offers optimal conditions with negligible damage to the RBC with effective drug loading (Sahoo et al 2017). RBCs do not have internalization pathways which pose a challenge during this process.…”
Section: Encapsulation Of Nanoparticle In Rbcsmentioning
confidence: 99%
“…Encapsulation process involves isolation of RBCs, loading of drug and infusion into the body for effective delivery and metabolism at the target site. This process involves different surface chemistries, shapes to the surface of RBC and compositions which offers optimal conditions with negligible damage to the RBC with effective drug loading (Sahoo et al 2017). RBCs do not have internalization pathways which pose a challenge during this process.…”
Section: Encapsulation Of Nanoparticle In Rbcsmentioning
confidence: 99%
“…This technique is not only suitable to be used for conjugation of therapeutic agents, but also can be used to conjugate nanoparticles on RBCm as demonstrated by Sahoo et al who successfully attached copolymer-based nanoparticles encapsulating fluorescent-BSA on the surface of RBCm using different GPA-specific targeting ligands, namely ERY1, scFv TER-119, protamine-based CPP without damaging RBCm. In vitro study showed that the protamine-based CPP was superior to the other ligands in binding nanoparticles on RBCm 68.…”
Section: Surface Engineering/functionalization Of Rbcmmentioning
confidence: 99%
“…In addition, the use of scFv of monoclonal antibodies is preferred to target the RBC receptors as it does not cause the harmful immune responses compared with the murine monoclonal antibodies. This technique has recently been used to conjugate nanoparticles to RBCs with no adverse effects on the oxygenation status of RBCs 68. Currently, Xie et al developed a technique to confirm the right-side-out orientation of RBCm coating by attaching a hidden peptide ligand derived from the cytoplasmic protein P4.2 (P4.2 peptide) to the band 3 proteins in RBCm.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Red blood cells (RBCs) have unique properties that make them attractive for allogeneic cell therapy, including inherent biocompatibility when O-negative donor blood is utilized 17 . This has led to their long-term use and familiar history in transfusion medicine with very few side effects 18 .…”
mentioning
confidence: 99%
“…Importantly, tumor control is associated with the development of long-term memory and epitope spreading, leading to efficacy against tumors that do not express the original target antigen but are otherwise identical. These functions led to the creation of a clinical candidate, RTX ™ -321, which expresses human leukocyte antigen (HLA)-A*02:01 with human papillomavirus (HPV) 16 E7 peptide [11][12][13][14][15][16][17][18][19] (HLA-A2-HPV), 4-1BBL, and IL-12. We show that RTX-321 induces the activation of HPV antigen-specific primary human T cells, and that all three signals are sufficient for robust effector function and differentiation of effector memory cells.…”
mentioning
confidence: 99%